2006
DOI: 10.1624/105812406x107807
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Learning Needs of Minority Expectant Women and Barriers to Prenatal Education

Abstract: This study explored the prenatal education needs of foreign-born, Hispanic, and minority expectant mothers in the United States who received their obstetric care at a hospital-based clinic. Their perceptions also helped identify barriers to attending childbirth education classes. Fifty-nine pregnant women in their first, second, and third trimesters of pregnancy participated in the study, which consisted of two separate surveys. Participants rated the importance of attending classes, as well as various topics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…These findings were similar to the results of other studies. Berman [20] reported that pregnant women ranked breastfeeding fourth among content considered most important to learn during pregnancy. In the study, 60% of first-time mothers considered breastfeeding "very important"; however, among mothers who already had one child, only 28.2% considered "very important".…”
Section: Profileof Knowledgeable Pregnantmentioning
confidence: 99%
“…These findings were similar to the results of other studies. Berman [20] reported that pregnant women ranked breastfeeding fourth among content considered most important to learn during pregnancy. In the study, 60% of first-time mothers considered breastfeeding "very important"; however, among mothers who already had one child, only 28.2% considered "very important".…”
Section: Profileof Knowledgeable Pregnantmentioning
confidence: 99%
“…Information obtained from healthcare providers is perceived as more useful and reliable than information sought on their own (Berman, 2006;Carolan, 2007). Information obtained from healthcare providers is perceived as more useful and reliable than information sought on their own (Berman, 2006;Carolan, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…The enrolled sample included a relatively equal number of White and Black women and a small Women in the perinatal period report seeking information from a variety of sources, including printed material, childbirth educators, family or female friends, and trusted healthcare providers (Berman, 2006;Shieh et al, 2009). The enrolled sample included a relatively equal number of White and Black women and a small Women in the perinatal period report seeking information from a variety of sources, including printed material, childbirth educators, family or female friends, and trusted healthcare providers (Berman, 2006;Shieh et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instructors also have the ability to explain why certain changes occur during pregnancy, while emphasizing how women's bodies are perfectly designed to nourish and nurture their babies through pregnancy. A study by Berman (2006) found that the majority of pregnant women in the study were interested in receiving information on discomforts, emotional changes, physical changes, and expectations and beliefs during the pregnancy. Kavanaugh and Hershberger (2005) found that expectant parents misread symptoms of pregnancy complications, which may have contributed to a pregnancy loss or neonatal death.…”
Section: Introductionmentioning
confidence: 99%